Pengaruh Kualitas Layanan dan Kesadaran Merek Terhadap Minat Beli Layanan Youtube Premium pada Mahasiswa di Kota Malang - Muhammad Ainul Yaqin; Ayu Sulasari; Musthofa Hadi (Teewan Journal Solutions, 2026)
Technological advancement has become a vital instrument in facilitating human needs, particularly in accessing entertainment and information. Among the most widely used platforms is YouTube, including its paid service, YouTube Premium, which offers an ad-free experience along with various exclusive features. The growth of a company is closely linked to consumers’ purchase intention toward its products or services. Several factors can influence purchase intention, notably service quality and brand awareness, which play essential roles in sustaining and enhancing consumer interest. This study aims to examine the effect of service quality and brand awareness on the purchase intention of YouTube Premium among university students in Malang City. Employing a quantitative approach with an explanatory research design, this study involved 120 respondents selected through purposive sampling. Data were collected using questionnaires distributed via Google Forms. The analytical techniques used include descriptive analysis, validity and reliability tests, classical assumption testing, and hypothesis testing. The findings reveal that both service quality and brand awareness significantly influence purchase intention, both partially and simultaneously.